The neural dynamics of competition resolution for language production in the prefrontal cortex. Issue 3 (19th December 2017) - Bourguignon, Nicolas J.; Ohashi, Hiroki; Nguyen, Don; Gracco, Vincent L.
Abstract: Previous research suggests a pivotal role of the prefrontal cortex (PFC) in word selection during tasks of confrontation naming (CN) and verb generation (VG), both of which feature varying degrees of competition between candidate responses. However, discrepancies in prefrontal activity have also been reported between the two tasks, in particular more widespread and intense activation in VG extending into (left) ventrolateral PFC, the functional significance of which remains unclear. We propose that these variations reflect differences in competition resolution processes tied to distinct underlying lexico‐semantic operations: Although CN involves selecting lexical entries out of limited sets of alternatives, VG requires exploration of possible semantic relations not readily evident from the object itself, requiring prefrontal areas previously shown to be recruited in top‐down retrieval of information from lexico‐semantic memory. We tested this hypothesis through combined independent component analysis of functional imaging data and information‐theoretic measurements of variations in selection competition associated with participants' performance in overt CN and VG tasks. Selection competition during CN engaged the anterior insula and surrounding opercular tissue, while competition during VG recruited additional activity of left ventrolateral PFC. These patterns remained after controlling for participants' speech onset latencies indicative of possible task differences in mental effort. These findings have implications for understanding the neural–computational dynamics of cognitive control in language production and how it relates to the functional architecture of adaptive behavior.